Nonlinear Association of Glycosylated Hemoglobin With Single Intracranial Aneurysm Rupture in Patients With Diabetes Mellitus: A Cross-Sectional Study - Su, Shi-Xing; Wang, Xue-Tao; Li, Xi-Feng; Duan, Chuan-Zhi; Bi, Yi-Ming; Zhang, Xin (Frontiers in Neurology, 2022)
BACKGROUND: Published literature linking diabetes mellitus (DM) to ruptured intracranial aneurysm (IA) have been controversial and limited by methodology. Thus, this study was performed to examine whether hyperglycemia control status is independently associated to single IA rupture in patients with DM. METHODS: We conducted a cross-sectional study at two Chinese hospitals between January 2010 to November 2017. The medical records of 223 single IA patients with DM were reviewed and analyzed. We used glycosylated hemoglobin (GHB) as interested independent variable, and the outcome variable was ruptured status of IA. Covariates included data of demographics, morphological parameters, lifestyle habits, clinical features and comorbidities. RESULTS: Multivariable adjusted binary logistic regression and sensitivity analyses indicated GHB was not associated with IA rupture (Odds ratio (OR)=1.05, 95%CI 0.83 to 1.32). A non-linear association between GHB and IA rupture was observe, whose inflection points were 5.5 and 8.9. The OR values and the confidence intervals were 0.37(0.15 to 0.88) at the range of 1.88 to 5.5% of GHB, 1.57 (1,01, 2.44) at the range of 5.5 to 8.9%, and 0.40 (0.05 to 3.25) at the range of 8.9 to 10.1, respectively. CONCLUSION: The independent correlation between GHB and risk of IA rupture presented is nonlinear. The good blood sugar control in single IA patients with DM can reduce the risk of IA rupture, and vice versa.